Two new species of Anastrepha (Diptera: Tephritidae) from Ecuador - Troya, Henry; Norrbom, Allen L.; Pineda, Julia E. Bolanos (Zootaxa, 2020)
Despite the fact that many species are economically important agricultural pests, the fruit fly fauna of Ecuador is still relatively poorly known. To better understand this fauna and the distribution and host plants of the pest species, the Proyecto Nacional de Manejo de las Moscas de la Fruta of AGROCALIDAD has conducted trapping surveys in many parts of the country. Two new species of Anastrepha from Ecuador that were collected by this project are described and illustrated: A. quadripuncta Troya & Norrbom and A. tinctobasis Troya & Norrbom. A new species group, the morvasi group, is recognized for A. morvasi Zucchi and A. quadripuncta.